2009
DOI: 10.1159/000231986
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Renal Failure in ICUs: A Multi-Center Prospective Study

Abstract: Background and Aim: Acute kidney injury (AKI) is a common complication in intensive care units (ICUs). However, its incidence and outcome vary in several studies depending on definitions used or even the geographic origin of the study. We aimed to evaluate the epidemiology of AKI in ICUs in Greece. Method: Prospective multicenter study of ICU patients presented with AKI during a 3-month period. Results: One-hundred and seventy patients presented with AKI (16% of total admissions in 23 ICUs). The most common co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 66 publications
0
26
1
2
Order By: Relevance
“…However, our findings (19) are different from those of Wald et al (4) as well as many of the previous observational studies (1,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Instead, our findings are more consistent with previous RCTs (1,15,16,(30)(31)(32)51,52).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our findings (19) are different from those of Wald et al (4) as well as many of the previous observational studies (1,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Instead, our findings are more consistent with previous RCTs (1,15,16,(30)(31)(32)51,52).…”
Section: Discussioncontrasting
confidence: 99%
“…However, several of these trials had limitations, including small sample sizes, inability to control for major clinical decisions, and inability to control for other supportive management strategies that affect outcomes in AKI (e.g., nutrition support, hemodynamic support, timing of initiation of RRT, and dose of dialysis) (4,25,27). Previous observational studies have suggested that initial modality of RRT may affect renal recovery in AKI, with a higher rate of dialysis dependence seen among survivors who initially received IHD versus CRRT (1,4,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). These discrepant findings could be caused by inherent biases in observational studies that are not present in RCTs, such as imbalances between groups and differential mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] AKI is especially common in critically ill patients in the intensive care unit (ICU) and occurs in up to 67% of ICU admissions, depending on the definition used. [4][5][6] Five to six percent of patients with AKI in the ICU require renal replacement therapy (RRT). 5,7 AKI requiring RRT is associated with a very high mortality rate ranging from 50 to 83%.…”
Section: Introductionmentioning
confidence: 99%
“…Severe sepsis and septic shock are life-threatening complications of infections [1] and are the most common causes of death in intensive care units [2][3][4] . The high morbidity and mortality rates associated with sepsis urgently call for novel therapies.…”
Section: Endothelial Bioreactor Ameliorates Endotoxemia Sepsis In Swinementioning
confidence: 99%